Factors Effecting the Capital Adequacy Ratio of Banking System of Bosnia and Herzegovina and Croatia: Factors Effecting the Capital Adequacy Ratio of Banking System of Bosnia and Herzegovina and Croatia - Alihodžić, Almir; Nadžaković, Elman (Industrija, 2023)
The importance of minimum capital adequacy ratios in preventing banks from going bankrupt and losing depositor money is underscored by their ability to absorb a reasonable amount of losses. This work contributes to the literature on bank capital and, in particular, delivers a thorough analysis of bank capital in Bosnia and Herzegovina and Croatia contexts. This analysis refers to the strand of literature on non-performing loans and bank capital that has been of continuous interest to researchers. It is a relevant area of research because it discusses the most important part of the banking business, especially in the context of increasing global competition and crises. In this scientific area, we inquire whether and how leverage rate, gross domestic product rate, and return on equity affect the capital adequacy ratio. In this respect, this study advances the literature of effects on bank capital that have not been analysed by other scholarly contributions, especially as it discusses the impact of leverage rate, gross domestic product rate, and return on equity in the context of the entire banking systems of Bosnia and Herzegovina and Croatia. The study is limited to a six-year period from 2016 to 2021. Empirical evidence based on the application of a model suggests that both countries resulted in different correlations between countries. Modelling was done to determine the relationship between the independent variables LR, GDP Growth, ROE, and effect on CAR. In addition, the capital adequacy ratio proves to be more and more important for banks.